FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN DI KECAMATAN JATIBARANG KABUPATEN BREBES - Briliany, Ghina Khoirunisa; Rohman, Abdul (Diponegoro Journal of Accounting, 2024)
This research aims to determine the influence of tax knowledge, quality of tax services, and village head leadership on taxpayer compliance in Jatibarang District, Brebes Regency. This research was conducted using a survey method using a questionnaire distributed to taxpayers in Jatibarang District, Brebes Regency. The data obtained was processed using the SPSS application with descriptive analysis data processing and multiple regression analysis. The sample used in this research was 97 taxpayers in Jatibarang District, Brebes Regency. The research results show that tax knowledge, the quality of tax services, and the leadership of the village head have a positive and significant influence on taxpayer compliance. It is hoped that this research will provide an illustration that there are several factors that need to be pursued in order to increase taxpayer compliance in order to realize increased tax revenues.